The teaching of sex education in Higher Secondary schools in Qeshm Island-Iran : teachers' perception - Daryanavard, Soraya (Kulliyyah of Education, International Islamic University Malaysia, 2018)
Sex education is an important element of the educational process in social life which plays a great role in saving young generations from ethical deviations and sexually transmitted diseases. This study investigates the perceptions of teachers of Higher Secondary schools in Qeshm Island-Iran on sex education and how they implement teaching sexual issues among their students. It also explores the teachers' perceptions on important topics and resources that should be covered and used in sex education. The study also identifies the challenges faced in teaching sex education and possible approachess in teaching school-based sex education in Qeshm Island. This study employed a qualitative research method to collect and analyze data utilizing semi-structured interview for data collection. The findings showed that risky sexual behaviors among students and their outcomes generally result from lack of correct knowledge about sexuality. Most of the teachers trusted that the ideal individuals for instructing sexual issues to youths are teachers and the best time to begin sex education is when students are in secondary school before reaching adulthood. The results also showed that most of the teachers suggested that there should be a proper subject for sex education in the School curriculum, however, on the other hand a few teachers said that it should be discussed more under the Ahkam and Fiqh subjects. Finally, the study recommends more attention to be given to sex education especially among students to compensate for the existing deficiencies and to reduce the sexual problems caused by lack of information about sexuality.